Research on the Impact of Digital Finance Development on Commercial Credit Financing Between Enterprises - Zhao, Zhuoran (Transactions on Economics, Business and Management Research, 2024)
Digital finance has effectively solved the financial exclusion dilemma and eased the financing constraints of enterprises, but its impact on business-to-business commercial credit financing remains to be tested. Taking China’s A-share non-financial listed companies from 2011 to 2019 as the research object, we empirically test the impact of digital finance development on inter-firm commercial credit financing. The results show that the development of digital finance inhibits inter-firm commercial credit financing behavior. The lower the degree of industry competition, the higher the supplier concentration, and the higher the customer concentration, the stronger the inhibitory effect of digital finance on inter-enterprise commercial credit financing. Bank credit based on supply chain plays a partial intermediary role in the process of digital financial development affecting inter-enterprise commercial credit financing; digital financial technology promotes the development of supply chain financial services of banks, inhibits the demand for inter-enterprise financing through commercial credit, and is able to alleviate the problem of inter-enterprise occupancy.